Pengaruh Religiusitas, Budget Constraint, Dan Penggunaan Media Sosial Terhadap Perilaku Konsumsi Muslim Di Kecamatan Tanjung Morawa - Friska, Nur Rani; Arif Lubis, Fauzi; Ria Armayani Hasibuan, Reni (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This research aims to determine whether there is an influence of religiosity, budget constraints and the use of social media on Muslim consumption behavior in Tanjung Morawa sub-district. The data collection sources used are primary data and secondary data. The respondents in this research were Muslim housewives in Tanjung Morawa sub-district. The number of villages or sub-districts in Tanjung Morawa sub-district is 26 villages or sub-districts and 100 housewives were used as samples. Data processing in this research uses SPSS 25 for Windows. The analysis used in this research is multiple linear regression analysis. The research results of R Square (R²) were 0.858 or 85.8%. Based on the results of the t test for the religiosity variable (X1) it has a significant effect on Muslim consumption behavior in Tanjung Morawa sub-district with a significance of 0.000 and t count of 8.368, for the Budget Constraint variable (X2) it has no significant effect on Muslim consumption behavior in Tanjung Morawa sub-district with significance 0.876 and t count of 0.157, for the Social Media variable (X3) it has a significant effect on Muslim consumption behavior in Tanjung Morawa sub-district with a significance of 0.000 and t count of 13.703. The results of the multiple linear regression test obtained the equation Y = -1.624 + 0.385X1 + 0.008X2 + 0.352X3y